EDUCATION INNOVATION EFFORTS IN IMPROVING TEACHER COMPETENCY IN TULUNGAGUNG, EAST JAVA - Suyitno Suyitno (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2015)
This study focuses on how education innovation efforts in teacher competency improvement was done through teacher peadagogic, personal, social, and professional competencies empowerment. This research is a field research using a qualitative approach conducted in Tulungagung, East Java dated January to June 2013. Result of this research was that the Education Department of Tulungagung District has made education innovation in serious efforts to improve teachers' competence, including: (1) Educational seminars, (2) Teacher training, (3) Intensive teachers professional development, (4) Teachership Workshop, (5) Subject teacher group discussion strengthenment, (6) Learning design and approach training, (7) Classroom Action Research Training, and (8) Intensive supervision, such as empowerment of teacher peadagogic, personal, social, and professional competencies.